Unique relationship between optimum compaction properties of fine-grained soils across rational compactive efforts: a validation study - O'Kelly, Brendan (My University, 2024)
Among the many proposals for estimating the compaction characteristics of fine-grained soils for different compaction energy levels (CELs), energy conversion (EC) models are gaining increased attention. These models work on the premise of employing measured optimum moisture content (OMC) and maximum dry unit weight (MDUW) values obtained for a rational CEL (e.g., standard or reduced-standard Proctor (SP or RSP)) to predict the same for other CELs. This study revisits the most recently proposed EC-based compaction modeling framework, critically examining its asserted accuracy and hence identifying its true potentials. This was achieved by performing comprehensive statistical analyses on a newly compiled database of 206 compaction test results, entailing 70 different fine-grained soils (with liquid limits ranging 19–365%) and accounting for CELs of 202.0–2723.5 kJ/m3. It was demonstrated that 99% and 96% of the differences between the SP-converted and measured values for OMC and MDUW, respectively, fall within the allowable margins of OMC and MDUW measurement errors permitted by the Australian AS 1289.5.1.1/AS 1289.5.2.1 standards (satisfying their recommended ≥ 95% requirement). Equally favorable results were also obtained for the RSP-based conversions. These findings reaffirmed that the optimum compaction parameters across rational CELs are somewhat uniquely related, and the effects of fine-grained soil attributes on soil compactability are adequately captured/explained by the measured OMC and MDUW values employed as the conversion inputs/predictors.
PUBLISHED
Keywords: Smart & Sustainable Planet; COMPACTION; GEOTECHNICAL ENGINEERING; Geotechnical Engineering; Geotechnics; SOIL PARAMETERS; Soil Mechanics; Soil Mechanics & Foundations; fine grained soil; geotechnical; soil improvement; soil stabilization